Perbandingan Model Pembelajaran Team Assisted Individualization dengan Model Pembelajaran Two Stay Two Stray Terhadap Hasil Belajar Matematika - Nur Fitriyah Indraswari; Maulidatul Hikmah; Fitriana Minggani (Musamus University, 2020)
The purpose of this study is to determine whether or not the differences in mathematics learning outcomes using the TAI learning model with TS-TS on functional derivative material. This research used a True-Experimental Design approach in the form of Posttest-Only Control Design. The population taken is all students of class XI-MIPA MAN Sumenep with sample class XI-MIPA 2 as experimental class I and class XI-MIPA 4 as experimental class II. The instrument used is in the form of TKAkh questions (Final Capability Test). Data analysis was performed using a t-test with a significance level of 5%. The results showed that the t-test is more than t-table, meaning that there were differences in mathematics learning outcomes using the TAI learning model and the TS-TS learning model on the functional derivative material